2019
DOI: 10.1538/expanim.18-0139
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of 21 experimental chicken lines with diverse origins and genetic backgrounds

Abstract: The genetic characteristics and diversity of 21 experimental chicken lines registered with the National BioResource Project of Japan were examined using mitochondrial D-loop sequences and 54 microsatellite DNA markers. A total of 12 haplotypes were detected in the 500-bp mitochondrial DNA sequences of the hypervariable segment I for 349 individuals of 21 lines. The 12 haplotypes belonged to three (A, D, and E) haplogroups, out of the eight (A‒H) common haplogroups in domestic chickens and red junglefowls. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Both the JB and congenic GSP/Cp strains exhibited the Cp trait. The GSP/Cp strain expresses a Cp allele that was introduced from the JB strain into a highly inbred strain derived from the Fayoumi breed, GSP, whose average heterozygosity is <0.01 for >50 microsatellite DNA markers 17 ( Supplementary Figs. 1-4 and Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the JB and congenic GSP/Cp strains exhibited the Cp trait. The GSP/Cp strain expresses a Cp allele that was introduced from the JB strain into a highly inbred strain derived from the Fayoumi breed, GSP, whose average heterozygosity is <0.01 for >50 microsatellite DNA markers 17 ( Supplementary Figs. 1-4 and Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The following three chicken strains were used for this study: the JB strain derived from the Japanese bantam breed "Chabo" that has the Creeper (Cp) trait ( Supplementary Fig. 1); and the GSP and PNP/DO strains, both of which are highly inbred strains derived from the Fayoumi breed 17,50,51 . All lines are maintained at the Avian Bioscience Research Center (ABRC), Nagoya University, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, despite using dayold chicks, our handling test effectively revealed the aggressive nature of OSM. Another interesting breed is PNP, a highly inbred line derived from three roosters and two hens of the Fayoumi breed, which has been maintained as a closed breeding colony with several pairs per generation [18]. PNP exhibited more exploratory behavior and higher locomotor activity compared to other breeds, indicating a bustling nature.…”
Section: Discussionmentioning
confidence: 99%
“…The positions of the DY line and Saitama population and the monophyly of the six farm populations from Aichi prefecture on the Dc tree indicated that the Dc tree is more reliable. In our previous study on the genetic characterisation for laboratory chicken lines, the Dps genetic distance constructed less realistic phylogenetic trees than that of Da genetic distance (Nunome et al, 2019). The Dc and Da genetic distances are known to be better estimators for topology construction (Takezaki & Nei, 1996).…”
Section: Genetic Relationships and Breeding Histories Of Farm And Lmentioning
confidence: 99%